طريقة التعلم المقلوب في تعليم اللغة العربية (دراسة وصفية عن تطبيقه في المدرسة المتوسطة مفتاح القلوب باميكاسان) - Fadoli, Ach. (Ihya al-Arabiyah: Jurnal Pendidikan Bahasa dan Sastra Arab, 2023)
Learning Arabic cannot be looked at as trivial, not as easy as imagined, learning Arabic requires innovative creative methods and strategies to improve students' abilities and make the class fun and not boring. Flipped classroom is a learning strategy that is present as a post-pandemic solution for the Covid-19 pandemic that combines online and offline learning, Flipped classroom is a method that can be said to be new, with the development of technology making this method increasingly attractive to most teachers, this method requires students to study first before entering the learning process in class. The purpose of this study is to describe the application of the flip classroom method at Miftahul Qulub Middle School, this type of research is qualitative using descriptive analytical methods, while the methods used in data collection are observation and interviews. The results of this study state that the implementation of the flipped classroom is divided into two, namely the pre-class stage and the class stage.